Design and Implementation of Internet of Things (IOT)-Based Fuel Level Monitoring and Management System - Mulenga , Peter; Halubanza, Brian (Proceedings of International Conference for ICT (ICICT) - Zambia, 2025)
Fuel level monitoring in Zambia continues to rely on outdated manual methods, such as dipsticks, which are inaccurate, inefficient, and prone to theft and mismanagement. This study presents the design and implementation of an Internet of Things (IoT)-based Fuel Level Monitoring and Management System (FLMMS) aimed at automating real-time fuel tracking and management. The system employs ultrasonic sensors, a fuel level sensor , Arduino Uno, GSM/GPRS modules, and a dynamic web platform to detect and relay fuel levels and abnormal consumption events. Real-time alerts via SMS and web dashboards enhance operational oversight. Testing showed a 98% accuracy rate and system uptime of 96%. The FLMMS offers a scalable, low-cost, and efficient solution adaptable to Zambia’s infrastructure, bridging critical gaps in fuel security, transparency, and data-driven management.